(untitled) (International Journal of Built Environment and Sustainability, 2022)
In the current century, due to global warming, pollution, climate change and the exponential growth of the world population, water resources are consumed at alarming rates. For this reason, sustainable methods of water harvesting have become an important research topic of today. In built environments, which are known to account for a significant share of total water consumption, places the development of alternative solutions for the acquisition and effective use of water to the forefront of the agenda. On the other hand, “nature” offers clues about how plant and animal species manage to use limited water resources with sustainable methods while also providing innovative solutions for “water harvesting”. In this context, this research seeks to answer “Can water harvesting strategies of living organisms that manage to obtain water via sustainable methods be transferred to building design through biomimicry?” In this direction, considering the potentials of biomimicry in architecture, plants and animals that are successful in water harvesting have been researched. In addition, biomimetic designs inspired by these living organisms have been analyzed. As a result of this analysis, it has been concluded that, with the use of biomimetic design techniques effective water harvesting methods can be developed for buildings